Humoral immune response to antigens of Porphyromonas gingivalis ATCC 33277 in chronic periodontitis - Mônica Franca; Lília Moura-Costa; Roberto J. Meyer; Soraya C. Trindade; Urbino da Rocha Tunes; Songelí M. Freire (University of São Paulo, 2007)
Introduction: Periodontitis is a chronic disease that results from an interaction of a mixed bacterial challenge and the host response. Objective: The purposes of this study were to evaluate the IgG serum levels to Porphyromonas gingivalis antigens by ELISA in individuals with different periodontal conditions correlated with clinical parameters, and to analyze the immunoreactivity profiles by Western blotting. Methods: Serum IgG levels against the cell sonicate antigen from P. gingivalis ATCC 33277 of 28 patients with chronic periodontitis (CP), 10 patients with gingivitis (G) and 21 periodontally healthy individuals (H) were measured by ELISA and Western immunoblotting. Results: In the CP group, sera reactivity by ELISA was significantly higher than in the G and H groups (Kruskal-Wallis p<0.001; Dunnet t3 p= 0.001 and Dunnet t3 p= 0.0001). There was no statistically significant difference between G and HP reactivity (Dunnett t3 p=0.617). Among individuals with chronic periodontitis, the IgG-anti-P. gingivalis serum levels were positively correlated with percentage of clinical attachment level =5mm (r s = + 0.375, p<0.05) and a negative correlation was found between IgG-anti-P. gingivalis levels and percentage of probing pocket depth 0-3mm (r s = - 0. 411, p< 0.05). The analysis of sera immunoreactivity profiles to sonicate antigen by Western blotting showed differences between the sera of CP, G and H group individuals. The serum from CP frequently reacted with high molecular weight (103 kDa, 86 kDa, 72 kDa, 60 kDa, 58 kDa, 52 kDa) protein fractions. Conclusions: Serum levels of IgG anti-P. gingivalis distinguished individuals with chronic periodontitis, gingivitis and healthy periodontium. There was a correlation between clinical parameters and serum IgG levels against P. gingivalis. There was a difference in the recognition profile of protein fractions among the studied groups and some bands were more specific